Intermedial Correspondence: A.G.M. – Ljudevit Šeštić and Josip Leović - Mrkonjić, Anđelko (Poznańskie Studia Slawistyczne, 2014)
The content of the paper examines the intermediate dialogue of the poetic and artistic text on the paradigm of A.G. Matoš’s poetry and the painting created by Ljudevit Šestić and Josip Leović. The main thought derives from Miroslav Šincel’s ascertainment how the works of Matoš „mirror the most important features of our symbolical-impressionistic modernism”. Šestić’s continental landscape impressionist painting and Leović’s symbolism in his painting, open therefore the possibility of intermediate style, content and biographical link (Tovarnik, Osijek, Đakovo, Paris, music...), keeping in mind the different positioning on the map of national cultural heritage. And with Matoš’s pictorial construction of lyrical text and his artistic sensibility, that is very much possible. In the field of stylistic link, purity of style can be read out, but also stylistic impurities caused by a personal and Homeland fate. This paper is of culturological nature.